Role of Religious Education Institutions in West Kalimantan Social Life, Multicultural Education, and Religious Moderation - Yapandi Yapandi; Rustam A (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This paper is a study related to the role of religious education institutions, this research is qualitative research with a phenomenological and descriptive approach while the data obtained through the results of interviews and conducting surveys to religious education communities and institutions in West Kalimantan. This research shows that the presence of Religious Education Institutions has a very important role for society. This is evidenced by the results of a survey conducted by the Board of Education for the Religious Education Commission which revealed that at least the presence of Religious Education Institutions has a very deep role related to its existence in the midst of society. The thing that considers the Curriculum that considers about resolving Potential Conflicts is considered very active by existing Religious Education Institutions, as for the form of curriculum that refers to KMA 183 and 184. While the Multicultural Education Curriculum that becomes a guideline is religious moderation.